The problem of extremism among the youth (by the materials of a sociological study in the Republic of Dagestan) - G.M. Dzhamaludinov; Sh.G. Seidov; A.G. Khaybulaeva; M.Sh. Abdusalamova (Известия высших учебных заведений. Поволжский регион: Общественные науки, 2023)
Background. At the beginning of the 21st century, the problem of terrorism and religious and political extremism has acquired global significance. Currently, numerous manifestations of extremism violate the stability of socio-political life and pose a threat to the security of the entire world community. In this regard, it is necessary to monitor public opinion about threats and attitudes to extremist activities, which would allow us to develop an effective system for countering extremism and preventing terrorism. In this aspect, it is important to work with the younger generation. The purpose of the study is to analyze the causes of the emergence and growth of religious and political extremism among high school students, as well as their parents and teachers. Materials and methods. The materials used are: the results of the author’s research of high school students and their parents in schools of the Republic of Dagestan (2021); the results of the secondary analysis of All- Russian studies: FOM (Public Opinion Foundation, VTsIOM (the Russian Public Opinion Research Center). Results. Based on the conducted research, it was revealed that among the most significant causes of terrorist activity, in particular on the territory of the Republic of Dagestan, are socio-economic problems (unemployment, poverty, corruption), as well as religious reasons. These causes are closely interrelated, and they can be affected through the prevention of terrorism, primarily through joint efforts in the fields of education and upbringing. The opinions of parents and teachers agree that the most effective directions in this case are solving the problems of youth (unemployment, standard of living), improving the quality of education at school, education in the spirit of patriotism and law-abiding. Conclusions. According to the results of the study, it is concluded that comprehensive measures are needed both at the federal level and at the personal level. The main groups of measures to prevent extremism and terrorism include: socio-economic, legal, information and propaganda.